Theory, evaluation, and practice in widening participation: A framework approach to assessing impact (UCL Press, 2016)
The English higher education (HE) system is deeply stratified, with younger students from more privileged backgrounds comprising the majority of the student population. Over the last 15 years considerable investment has been made to widen participation but attempts to evaluate these initiatives and demonstrate impact have presented a major challenge for the HE sector. This paper explores the development and application of a framework for evaluating and researching university-led interventions. Drawing largely on the theoretical work of Bourdieu it provides a basis for designing and evaluating programmes and activities to develop student cultural capital and habitus, and foster agency and a sense of belonging in HE settings.